2017
DOI: 10.3390/ijgi6110345
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Tourist Behavior Patterns by Travel Motifs and Geo-Tagged Photos from Flickr

Abstract: Abstract:With millions of people traveling to unfamiliar cities to spend holidays, travel recommendation becomes necessary to assist tourists in planning their trips more efficiently. Serving as a prerequisite to travel recommender systems, understanding tourist behavior patterns is therefore of great importance. Recently, geo-tagged photos on social media platforms like Flickr have provided a rich data source that captures location histories of tourists and reflects their preferences. This article utilizes ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 33 publications
1
29
0
1
Order By: Relevance
“…Several alternative sources of social sensing data, including POIs [30], check-in data with location information [40,41], mobile phone data [25], and trajectory data [42], can then be applied to replace the MPPD data. A similar approach that fuses remote sensing and various social sensing data can be used to obtain a land use map.…”
Section: Advantages Of the Fused Land Cover Map And Future Workmentioning
confidence: 99%
“…Several alternative sources of social sensing data, including POIs [30], check-in data with location information [40,41], mobile phone data [25], and trajectory data [42], can then be applied to replace the MPPD data. A similar approach that fuses remote sensing and various social sensing data can be used to obtain a land use map.…”
Section: Advantages Of the Fused Land Cover Map And Future Workmentioning
confidence: 99%
“…Previous studies that utilize online photographs for inferring nature-based human activities have a diverse research focus. Some examples include, but are not limited to, identifying character of landscapes [4], land cover and land use [5], recreational demand in water resources [1], events and tourist hotspots [6][7][8], impact of rare species in tourism [9], common tourist trajectories [10,11], recreational visitation at national parks [3], the perceived aesthetic value of ecosystems [12,13], as well as the relationship between cultural ecosystem services and landscape features [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…From posts on the NAVER blog in Korea, it was found that London, Paris, Venezia, and Firenze were key cities where Korean backpackers tended to enter Europe [26]. Tourist trajectories were extracted from Flicker's geo-tagged photos and then motif tourist mobility patterns were detected [27]. Wu et al introduced a tourism hotspot network approach to investigate travel patterns from social media data for tourism resources planning [28].…”
Section: Introductionmentioning
confidence: 99%